A standardized biohydrogen potential protocol: An international round robin test approach. (8th October 2019) - Carrillo-Reyes, Julián; Tapia-Rodríguez, Aída; Buitrón, Germán; Moreno-Andrade, Iván; Palomo-Briones, Rodolfo; Razo-Flores, Elías; Aguilar Juárez, Oscar; Arreola-Vargas, Jorge; Bernet, Nicolas; Maluf Braga, Adriana Ferreira; Braga, Lucia; Castelló, Elena; et al.
Abstract: Hydrogen production by dark fermentation is an emerging technology of increasing interest due to its renewable feature. Recent scientific advances have well investigated the operational conditions to produce hydrogen through the valorization of several wastes or wastewaters. However, the development of standardized protocols to accurately assess the biohydrogen potential (BHP) is of crucial importance. This work is the first interlaboratory and international effort to validate a protocol estimating hydrogen potential using batch tests, using glucose as individual model substrate. The repeatability of the hydrogen potential (HP) increased with variations of the proposed protocol: reducing substrate concentration, increasing the buffer capacity, and using an automatic device. The interlaboratory variation of the HP was reduced from 32 to 12%, demonstrating the reproducibility and robustness of the proposed protocol. Recommendations to run BHP tests were formulated in terms of i) repeatability and reproducibility of results, ii) criteria for results validation and acceptance, iii) workload of the proposed protocols. Highlights: The standardized protocol for bioH2 potential was internationally validated. Substrate content and buffer capacity affect the repeatability and reproducibility. H2 potential fits the acceptance criteria of ≥14% of interlaboratory variation. Either the manual or automatic protocol fits the acceptance criteria.